Post a New Question

Math

posted by .

Express this function in vertex form by completing the square:
3x^2 - 4x + 1

PLEASE SHOW STEP BY STEP!!!

  • Math -

    Assume
    3x^2 - 4x + C to be a perfect square, (ax + b)^2, where a abd b are constants. The square would be
    a^2 + 2ab + b^2. Therefore
    a = sqrt3 and 2b sqrt3 = -4
    b = -2/sqrt 3
    b^2 = 4/3

    3x^2 - 4x + 1 = (x sqrt 3 - 2/sqrt3)^2 -1/3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question